TANGGUNG JAWAB SOSIAL PERUSAHAAN (CORPORATE SOSIAL RESPONSIBILITY) DITINJAU DARI PRINSIP GOOD CORPORATE GOVERNANCE PADA BADAN USAHA MILIK NEGARA (STUDI KASUS PT. BATUBARA BUKIT ASAM (PERSERO), Tbk) - , Dewinta Garnis Ekawati,SH, Prof. M. Hawin. S.H., LL.M. Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research aims to analyze the Corporate Social Responsibility of State Owned Firms, using the perspective of Good Corporate Governance as the foundations for operating procedure of State-Owned firm in Indonesia. Because of the State-Owned are subject to the decree of State-Owned Firm Ministry number: KEP-117/M-MBU/2002 related to the implementation of Good Corporate Governance in State-Owned Firm and State-Owned Firm with form of Limited Liability Company that subject to Law Number 40/2007 related to Limited Liability Company. In this case related to article 74 in obligation to do Corporate Social Responsibilities. The study was conducted with normative juridical approach and using the empirical juridical to complementing data. The normative juridical approach consists of library research on primary legal materials, secondary legal materials, and tertiary legal materials. On the other hand, the empirical juridical approach is realized in the research or facts in the field. Based on the research there are a few analysis results